La justicia del menor: edades penales, realidades y expectativas - PANTOJA GARCIA, Félix (Cuadernos de Trabajo Social, 1997)
Organic Law 4/92, that regulates the competencies and procedures of Juvenile Courts, gives the Prosecutor the competencies that without doubt may be considered to be for the protection of minors. Even the mentioned Law aims at establishing procedures for those younger than l6 and older than 12 who have violated criminal laws (Criminal Cede and special criminal laws) with the consequent expression of social reproof for their behaviour, there is no doubt that the procedural aim arising from a systematic interpretation of the Law a evidently educative, and hence the responsibility of the Prosecutor who presents at Court the imposition of a measure a necessarily protective The proposed Law en Juvenile Justice develops this idea further: the explanation el the reasons of the law is absolutely clear in the definition since the text aims al “a law whose sanctions are basically educative and not properly penal”.